(untitled) (Journal of the College of Education for Women, 2019)
Stop the search on the performance of the stylistic literary messages sent byAbu Mohammed Amer bin Said Altakrna to the kings of his time and Ullachhighlighting the method of the three levels is psychological and away the consigneeand the receiver Taster literary text.Level voice and rhythmic, which dealt with (alliteration and Naturalizationvoice, and repetition and parallelism, and rhyme and toning) and its impact on thetaste and the emotional art between the sender and the receiver Bashklah.Who has studied the structural level (introductory sentence order methods in themessages, generally have much style presentation and brief delays and actor, andthen end the moral and intellectual martyrdom and desalination hair or Altersl himand with him the importance of correlation.The semantic level. Studied metaphor and simile and metaphor and imagesintensive in order to influence the recipient.Find out and telegraphic messages and Altakrna Ffinetha high as well as themotives and purposes of the public to send these messages, which according tonews addressee interest and influence as reported by the insider and a researcher onart and creativity rhetorical.